Forest carbon trade in Malaysia: early assessment of awareness, knowledge, and constraints among forest owners - Jegatheswaran, Natkuncaran; Ratnasingam, Jegatheswaran; Zbiec, Marcin; Ioras, Florin; Liat, Lim Choon; Ab Latib, Hazirah (North Carolina State University, 2024)
Forest carbon credit project developments throughout the world can contribute to nature-based solutions to mitigate climate change. With Malaysia’s large forest endowment, a study was conducted to evaluate the awareness and knowledge among forest owners, and to identify the main constraints faced when venturing into forest carbon credit projects. A total of 75 companies in both forest plantations and natural forests were involved in the study. The results clearly suggest that knowledge and awareness of forest carbon credit projects is relatively low among forest owners. Hence, forest carbon credit projects development in the country is relatively slow and only a few projects have had serious development to the auction phase. The slow uptake of carbon projects is plagued by the low carbon credit price, lack of clarity in the national carbon policy, limited expertise and capability for project development, and the lack of financing mechanisms for project development. Forest owners prefer biomass production and timber production due to the higher economic returns. Against this background, policymakers as well as federal-state initiatives need to address the gaps with the forest carbon credit project development ecosystem, in order to facilitate and realize the full carbon sequestration potential of the country.